Transesophageal Echocardiography Reveals a Missed Right Atrial Aneurysm in a Patient with Atrial Septal Defect and Mitral Valve Prolapse - Chellappan, Subramanian (J Cardiovasc Echogr, 2020)
Right atrial (RA) aneurysms are rare entities reported in the literature. Affected patients are usually asymptomatic, but sometimes, they tend to present with arrhythmias or even heart failure if big. They may form a nidus for thrombus formation and subsequent thromboembolic complications. We report a coincidental finding of a RA aneurysm in a 22-year-old female with the atrial septal defect and mitral valve prolapse, causing moderate mitral regurgitation. The aneurysm was detected incidentally on transesophageal echo after anesthetic induction for elective surgery of the primary pathology. The mitral valve was repaired, and the atrial septal defect was closed. The aneurysm was excised in toto and RA wall repaired.